2014
DOI: 10.1017/s175173111300195x
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association study for calving traits in Holstein–Friesian dairy cattle

Abstract: Dystocia and perinatal mortality are quantitative traits that significantly impact animal productivity and welfare. Their economic importance is reflected by their inclusion in the national breeding goals of many cattle populations. The genetic architecture that influences these traits, however, has still yet to be thoroughly defined. Regions of the bovine genome associated with calving difficulty (direct and maternal) and perinatal mortality were detected in this study using a Bayesian approach with 43 204 si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 45 publications
3
20
0
Order By: Relevance
“…Many studies have reported on QTL affecting calving traits in several populations of Holstein cattle (Kühn et al, 2003;Schnabel et al, 2005;Holmberg and Andersson-Eklund, 2006;Kolbehdari et al, 2008;Thomasen et al, 2008;Seidenspinner et al, 2011;Purfield et al, 2014), and there appears to be a major gene on BTA18 affecting dystocia, stillbirth, conformation, and lifetime economic merit (Cole et al, 2009b;Brand et al, 2010;Sahana et al, 2011;Purfield et al, 2014). Qanbari et al (2011) also identified a signature of selection in the same region of the cattle genome.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have reported on QTL affecting calving traits in several populations of Holstein cattle (Kühn et al, 2003;Schnabel et al, 2005;Holmberg and Andersson-Eklund, 2006;Kolbehdari et al, 2008;Thomasen et al, 2008;Seidenspinner et al, 2011;Purfield et al, 2014), and there appears to be a major gene on BTA18 affecting dystocia, stillbirth, conformation, and lifetime economic merit (Cole et al, 2009b;Brand et al, 2010;Sahana et al, 2011;Purfield et al, 2014). Qanbari et al (2011) also identified a signature of selection in the same region of the cattle genome.…”
Section: Introductionmentioning
confidence: 99%
“…They verified previous QTL studies for calving ease, foetus size and calf mortality and concluded that chromosome 18 contains many significant SNP markers for fertility traits. Two years later, Purfield, Bradley, Kearney, and Berry () in GWAS confirmed the significant influence of SNP rs109478645 within SIGLEC5 on calving traits.…”
Section: Discussionmentioning
confidence: 88%
“…Positive correlations of dystocia with calf birth weights, 200-d weights, and post-weaning gain suggest that selection for carcass yield can have negative implications on reproductive performance in the cow herd due to increases in dystocia (Bennett & Gregory 2001a, Bennett & Gregory 2001b. A genome-wide association study identified chromosomal regions associated with calving traits in Holstein-Friesian cows (Purfield et al 2013). A polymorphism in the hedgehog interacting protein (HHIP) gene that is associated with stature in humans was associated with direct calving difficulty, although polymorphisms in the bovine HHIP gene were not associated with stature in cattle (Pryce et al 2011).…”
Section: Systems Based Investigations Of the Genetic Changesmentioning
confidence: 99%